Қарақалпақ халық эпосларында мифлик сюжетлик мотивлер - Есебаев, М (SCIENCE and SOCIETY, 2019)
The articale is devoted to the issues of inter connection and reasons of mythological motives in the poetic composition of the Kara- kalpak folk eposes. The author gives the comparative analysis in typological and artistic aspects of mythological motives in the plot of an epos.
Keywords: epos; myth; plot; witch; folklore; image; motive; prophet; jirau; bahshi (a national perfomer of folk (eposes) by musical instruments: kobiz; dutar)